PENGGUNAAN METODE KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VA SDN 021 TANJUNG PALAS KECAMATAN DUMAI TIMUR - Sejati ' (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low result of fifth grade students learn math SDN 021Tanjung Palas. The low learning outcomes due to: (a) students find it difficult to understandthe elements and properties of geometrical abstract; (B) how to deliver materials that arelacking attract students to understand the material I teach, always using methods lectures,discussion, assignments. This study aims to improve the learning outcomes of mathematicsthrough STAD cooperative method. This research is a class act, carried out by two cycles.The study states that hasila learning has increased, this is evidenced by the base score is thenumber of students who completed 16 students (44.4%), in the first cycle is the number ofstudents who pass the 25 students (69.4%). And the second cycle is the number of studentswho pass the 32 students (88.9%).